Geological Features Observations in Eastern Indonesia Based on Selected P3GL Seismic Data: A Report from FOSI-P3GL Seminar, Cirebon, January 31, 2018 - Herman Darman; Ricky Andrian Tampubolon; Mellinda Arisandy (Berita Sedimentologi, 2018)
On January 31st, 2018, FOSI (Indonesian Sedimentologists Forum) organized a one day seminar in Cirebon (West Java), hosted by the Marine Geological Institute of Indonesia (or P3GL: Pusat Penelitian dan Pengembangan Geologi Kelautan). P3GL is a government institution which operates research vessels called Geomarin III. Their surveys typically include seismic acquisition, magnetic data acquisition and seafloor sediment sampling in Indonesian water. The seminar was aimed to provide an overview of their data to the geoscience community, especially those in the petroleum industry as the data may help petroleum exploration activities in Eastern Indonesia. This article focuses on selected seismic data which were presented during the seminar.